Effects of new generation triptans – frovatriptan and almotriptan – on hemodynamic parameters in intact male and female rats - Saracheva Kremena; Hrischev Petar; Vasileva Liliya; Topolov Mariyan; Nikolova Julia; Getova Damianka (Acta Pharmaceutica)
The introduction of the second generation triptans in clinical and experimental practice was a major progress in the pharmacotherapy of migraine. Frovatriptan is a second generation triptan with strong 5-HT1B/1D serotonergic agonism and low 5-HT1A/7 receptor affinity, while almotriptan possesses not only the typical 5-HT1B/1D receptor agonist activity, but shows an affinity to the 5-HT1F receptor. The aim of our study was to assess the impact of frovatriptan and almotriptan on hemodynamics in male and female rats. We used a non-invasive “tail-cuff” method to measure the arterial blood pressure. Female and male Wistar rats were treated separately with high and low dosages of frovatriptan and almotriptan. Male and female rats showed reduction in all hemodynamic parameters, but only male rats showed an increase in the heart rate. In general, we could say that both almotriptan and frovatriptan potentiate cardiovascular safety.